2020
DOI: 10.1001/jamapsychiatry.2019.2896
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Suicide Research–Can It Improve Risk Factor Identification?

Abstract: Machine learning is on the rise. According to Scopus (www2. scopus.com), the number of publications in medicine with machine learning in the title, abstract, or as a keyword during 2016 to 2018 increased from 1658 to 3904. In psychiatry, applications of machine learning are proposed to improve the accuracy of diagnosis and prognosis and determine treatment choice. At the same time, much of this research has given insufficient attention to high-quality methods, clinical applications, and ethical aspects. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…There was a substantial overlap in top-ranked predictors between different models. While borderline personality disorder, substance use disorder, depression, dispensed benzodiazepines and/or antidepressants have already been identified as risk factors for suicide [ 38 , 39 ], the timing of these factors may play a vital role in predicting subsequent suicidal behavior [ 40 ]. Our study showed that temporally close predictors tended to be ranked higher than distal ones.…”
Section: Discussionmentioning
confidence: 99%
“…There was a substantial overlap in top-ranked predictors between different models. While borderline personality disorder, substance use disorder, depression, dispensed benzodiazepines and/or antidepressants have already been identified as risk factors for suicide [ 38 , 39 ], the timing of these factors may play a vital role in predicting subsequent suicidal behavior [ 40 ]. Our study showed that temporally close predictors tended to be ranked higher than distal ones.…”
Section: Discussionmentioning
confidence: 99%
“…The aim was to improve identification and prevention of suicidality; however, to date, the evidence is still weak for this purpose due to small sample sizes, heterogeneity and inconsistency across studies, and, as further shown in this study, small effects sizes with limited predictive value. There is therefore an urgent need to improve the study of neurobiological biomarkers, possibly in conjunction with psychosocial risk factors, using other methodologies such as machine learning 61,62 . That said, what our results show is that vulnerability to suicidality does not appear to have a “brain signature” with a strong enough effect in school-age children.…”
Section: Discussionmentioning
confidence: 99%
“…ML algorithms are designed to maximize their clinical significance and generalization potential. In fact, ML models have been shown to be able to predict suicide tendencies [ 27 ]. Although ML algorithms have improved the accuracy of suicide risk detection; for a number of reasons, perfect predictions using ML are not possible and result in false positives and false positives [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Item 9 is widely used as a suicide screening tool; however, no studies have assessed the efficacy of PHQ-9 as a suicide screening tool using machine learning (ML) techniques. Machine learning algorithms have been proposed to improve diagnostic and prognostic accuracy and determine treatment options [ 27 ]. Various machine learning studies are focused on suicide prediction [ 28 , 29 , 30 ] and machine learning analysis has an advantage in its accuracy and scalability compared to conventional statistical approaches [ 29 ].…”
Section: Introductionmentioning
confidence: 99%